The Effect of Health Promotion using Audio Visual Media on Knowledge about Personal Hygiene in Class VI (JURNAL PROTEKSI KESEHATAN, 2025)
Currently, the problem that occurs in school age children is lack of Personal Hygiene. Lack of Personal Hygiene can be overcome by promoting health. This research aims to determine the effect of health promotion using audio-visual media on students' knowledge at SDN 020 Rambah Hilir. This research uses a pre-experimental method with a one group pre-test and post-test research design. With a sampling technique, namely total sampling, where the population and sample are the same, namely 56 people. The research results from data analysis mean students' knowledge about Personal Hygiene before health promotion was carried out was 74.91 while the average knowledge of students about Personal Hygiene after health promotion was carried out was 86.44. Based on the results of the T-Dependent statistical test data, a value (P-value 0.000) < 0.005 was obtained, which means that there is an influence of Health Promotion with audio visual media to increase students' knowledge about personal hygiene.